ANALYSIS OF FINANCIAL INCLUSION THROUGH FINTECH INNOVATION - Ramadhani Puspita Sari; Imronudin (Journal of Management and Islamic Finance, 2022)
This study aims to explain the intention in using mobile money through the application of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model. This research was conducted throughout the Solo Raya community. The number of samples in this study were 100 respondents. The data collection method used non-probability sampling with purposive sampling in which the researcher determines sampling by providing specific criteria. The research data was obtained through a survey method with a questionnaire technique. The analytical tool used to test the hypothesis was path analysis with the help of SmartPLS 3.0. The results show that the variable performance expectations, effort expectations, social influence, hedonic motivation, and facility conditions have no significant effect on the intention to use mobile money. Price value and habit variables have a positive and significant effect on the intention in using mobile money.